2016
DOI: 10.1038/ncomms12788
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of hydroxylated C24- and C26-acyl-chain sphingolipids mediates PIN2 apical sorting at trans-Golgi network subdomains

Abstract: The post-Golgi compartment trans-Golgi Network (TGN) is a central hub divided into multiple subdomains hosting distinct trafficking pathways, including polar delivery to apical membrane. Lipids such as sphingolipids and sterols have been implicated in polar trafficking from the TGN but the underlying mechanisms linking lipid composition to functional polar sorting at TGN subdomains remain unknown. Here we demonstrate that sphingolipids with α-hydroxylated acyl-chains of at least 24 carbon atoms are enriched in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
106
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(115 citation statements)
references
References 74 publications
9
106
0
Order By: Relevance
“…The TGN has been proposed to mature and be released from its association with the Golgi, generating an independent compartment that can deliver material to the plasma membrane (Viotti et al, 2010;Uemura et al, 2014Uemura et al, , 2019. Different coat proteins, soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs), tethering factors and lipids appear to define different subdomains of the TGN (Bassham et al, 2000;Chow et al, 2008;Gendre et al, 2011;Wattelet-Boyer et al, 2016;Renna et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The TGN has been proposed to mature and be released from its association with the Golgi, generating an independent compartment that can deliver material to the plasma membrane (Viotti et al, 2010;Uemura et al, 2014Uemura et al, , 2019. Different coat proteins, soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs), tethering factors and lipids appear to define different subdomains of the TGN (Bassham et al, 2000;Chow et al, 2008;Gendre et al, 2011;Wattelet-Boyer et al, 2016;Renna et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Two subclasses within the large A group of plant RABs, RABA2 and RABA3, identify a distinct TGN/EE membrane domain that functions in cargo delivery to the cell plate during cytokinesis (Chow et al, 2008). Whereas RABA2a defines TGN domains distinct from SYP61 vesicles, evidenced by differing lipid composition, RABA4b preferentially localizes to TGN SV sites together with SYP61, where it is involved in the transport of cell wall components (Preuss et al, 2004;Kang et al, 2011;Wattelet-Boyer et al, 2016;Jonsson et al, 2017). Another TGN domain harboring the secretory SNAREs VAMP721/722 and defined by RABA1 also has been suggested (Asaoka et al, 2013).…”
Section: Rab Gtpasesmentioning
confidence: 99%
“…Importantly, the authors established a novel link between a-hydroxylated acyl chain enrichment of TGN membranes and secretory trafficking, specifically in polarized transport to the apical membrane of epidermal cells (Wattelet-Boyer et al, 2016).…”
Section: Lipid Composition: An Independent Sorting Mechanism?mentioning
confidence: 99%
See 1 more Smart Citation
“…The haustorium is surrounded by host-derived membrane called the extrahaustorial membrane, which has modified endosomal characteristics . It has been shown that GIPCs are important for secretory sorting of proteins (Markham et al, 2011;Wattelet-Boyer et al, 2016), and therefore it may be that changes to a minor class of GPIC are enough to disrupt these processes, thereby negatively affecting G. orontii infection.…”
Section: Discussionmentioning
confidence: 99%